2022
DOI: 10.3389/fpsyg.2022.866682
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Based Relaxation Videos and Their Effect on Heart Rate Variability

Abstract: Growing evidence suggests that natural environments – whether in outdoor or indoor settings – foster psychological health and physiological relaxation, indicated by increased wellbeing, reduced stress levels, and increased parasympathetic activity. Greater insight into differential psychological aspects modulating psychophysiological responses to nature-based relaxation videos could help understand modes of action and develop personalized relaxation interventions. We investigated heart rate variability (HRV) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Multiple researchers have examined the impact of viewing nature on physical health as stress not only exhibits itself psychologically but also physically (e.g., sympathetic nervous activity dominance, greater heart rate and blood pressure, and increased alpha amylase and cortisol). In experimental studies, researchers have measured changes in physiology before and after indirectly exposing participants to nature through views of nature [ 65 , 66 ], virtual reality [ 15 , 53 , 67 , 68 ], videos [ 57 , 69 ], and sounds [ 17 , 68 ]. In several studies, after being indirectly exposed to nature, participants experienced greater parasympathetic nervous system dominance [ 65 , 66 , 68 ], heart rate variability [ 65 , 69 ], and decreased heart rate [ 15 , 53 , 66 , 68 , 69 ], systolic and diastolic blood pressure [ 17 , 53 , 67 ], skin conductance [ 53 , 65 ], pain [ 57 ], and cortisol [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple researchers have examined the impact of viewing nature on physical health as stress not only exhibits itself psychologically but also physically (e.g., sympathetic nervous activity dominance, greater heart rate and blood pressure, and increased alpha amylase and cortisol). In experimental studies, researchers have measured changes in physiology before and after indirectly exposing participants to nature through views of nature [ 65 , 66 ], virtual reality [ 15 , 53 , 67 , 68 ], videos [ 57 , 69 ], and sounds [ 17 , 68 ]. In several studies, after being indirectly exposed to nature, participants experienced greater parasympathetic nervous system dominance [ 65 , 66 , 68 ], heart rate variability [ 65 , 69 ], and decreased heart rate [ 15 , 53 , 66 , 68 , 69 ], systolic and diastolic blood pressure [ 17 , 53 , 67 ], skin conductance [ 53 , 65 ], pain [ 57 ], and cortisol [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In experimental studies, researchers have measured changes in physiology before and after indirectly exposing participants to nature through views of nature [ 65 , 66 ], virtual reality [ 15 , 53 , 67 , 68 ], videos [ 57 , 69 ], and sounds [ 17 , 68 ]. In several studies, after being indirectly exposed to nature, participants experienced greater parasympathetic nervous system dominance [ 65 , 66 , 68 ], heart rate variability [ 65 , 69 ], and decreased heart rate [ 15 , 53 , 66 , 68 , 69 ], systolic and diastolic blood pressure [ 17 , 53 , 67 ], skin conductance [ 53 , 65 ], pain [ 57 ], and cortisol [ 53 ]. In one study, after five minutes of viewing nature using virtual reality, the alpha amylase concentration decreased by 1.2 ng/mL and diastolic blood pressure by 4.6 mmHg [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Control group will be assigned to relaxation training, conducted at the same time each day as the experimental group during the 7-day period of intervention. The training will include watching documentaries of natural scenery without any other intervention, for which has been suggested a generic relaxation effect of video interventions on autonomic regulation [ 62 , 63 ]. The audio guidance and learning materials for both groups will be uploaded to the group chats separately, participants can practice at any time after the intervention period.…”
Section: Methodsmentioning
confidence: 99%
“…It is a helpful aid in becoming more mindful of our body, behaviour and emotion on a daily basis. The following is the adapted instruction of practicing STOP in confronting smoking cessation based on that developed by Liao [ 63 ]:…”
Section: Methodsmentioning
confidence: 99%
“…Overall, we set out to quantify the individual differences of cardiac vagal tone trends. Previous research found individual differences in HRV measures over time were due to external task demands and features (Smolders et al, 2012 ; Obradović and Finch, 2017 ; Blanck et al, 2019 ; Smith et al, 2019 ; Schwarck et al, 2021 ; Spangler et al, 2021 ; Tung et al, 2021 ; Benz et al, 2022 ), even with very low birth weight neonates (Padhye et al, 2009 ). Similarly, prior research has shown differences in autonomic activity in response to emotional stimuli when investigated as longitudinal trajectories—a feature not previously found when the autonomic activity was averaged across trials (e.g., Golland et al, 2014 ; Pasquini et al, 2022 ).…”
Section: Introductionmentioning
confidence: 97%